Clinical Characteristics and Surgical Features of Intracranial Fibrosarcoma. Issue 3 (May 2020) - Kang, Peng; Li, Pei-Liang; Peng, Jia-Yi; Ni, Ming; Jia, Gui-Jun; Jia, Wang
Abstract : Background: Intracranial fibrosarcoma is an extremely rare neoplasm in the central nervous system. Insofar there were only sporadic case reports describing its features. The purpose of this study is to review the clinical and surgical features of cases who were treated in our department. Method: The authors retrospectively reviewed and detailed the clinical and surgical data obtained from 5 patients with fibrosarcoma who underwent treatment at our institute between January 2009 and January 2019. Results: There were 3 males and 2 females including 2 juvenile and 3 senior patients. The most frequent sign was intermittent pain and vomiting. The location of the tumor included middle fossa, thalamus and midbrain, sellar and suprasellar region and right parietal-occipital lobe. Surgical observation demonstrated the consistency of the tumor was tenacious with abundant blood supply. Gross total resection was achieved in 2 cases. Pathological analysis showed spindle cells in a herringbone form with positive Vimentin staining in all 5 cases, with the absence of GFAP or S-100. All 5 patients were deceased eventually after a varied period of time after the first surgery. Conclusion: Intracranial fibrosarcoma was a highly malignant entity presented in the central nervous system. Surgery still remains the first-line treatment followed by radiotherapy, however, the prognostic outcome was very poor. Future studies should be more focused on accumulation of the relevant information on this disease thus hopefully in assisting to developing more optimized treatment. Abstract : Supplemental Digital Content is available in the text